Investigating Netizen Sentiment Toward Halal Certification in Indonesia Using Machine Learning - Yan Putra Timur; Ririn Tri Ratnasari; Anwar Allah Pitchay; Usman Jamilu (Universitas Airlangga, 2023)
ABSTRACT This study examined the most discussed halal certification terms and topics on Indonesian Twitter. This study also explored the sentiments and opinions of Indonesian netizens on halal certification. This analysis uses Twitter tweets from April 10 to 24, 2023. A quantitative method was used by using Orange Data Mining. Researchers used the keywords